Decentralizacja zadań oświatowych w kontekście wyzwań i oczekiwań społecznych - Raszewska-Skałecka, Renata (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Local government education of the Republic of Poland, as the part of decentralization of the state’s structure management, became one of the public task performed by tiers of local self-government. Decentralization of the public educational management adapts to improvement of organization and functioning of the Polish educational system, and to performing educational tasks, which function under the market economy conditions. Educational challenge, addressed to local self-government, is to find better ways of educational management, and ever greater society expectations, addressed to public administration, concern ways of performing educational tasks and bearing legal responsibility for the quality of education alservices
Keywords: local self-government; decentralization of educational tasks; educational policy; schoolmanaged by local self-government unit; educational management